Nilai-nilai Budaya Minangkabau dalam Novel Cinta di Kota Serambi Karya Irzen Hawer - Yolanda, Nadya; Gani, Erizal; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This study aimed to describe the values ​​of Minangkabau culture in the novel Cinta di Kota Serambi of Irzen Hawer work, which includes the value system of kinship between people and the value of human relationships. This research is a qualitative research with descriptive method that is content analysis. Sources of this study is novel Cinta di Kota Serambi of Hawer Irzen work. Data was collected through the steps: (1) read and understand the novel, (2) marking the Minangkabau cultural values ​​are reflected in the novel, (3) inventory data, and (4) to classify the data. Based on the results of this study revealed that (1) the value of kinship systems are discussed in the novel is found in only three of the eight types of kinship, ibu jo anak relationship, bapak jo anak and mamak jo kamanakan. Kinship already well established between ibu jo anak and bapak jo anak, but the relationship mamak jo kamanakan looks bad relationships, quarrels and disputes, (2) the value of relationships among humans in the novel is discussed among peers, students with teachers, between cousins​​, and landlady with men.